Analisis Risiko Investasi dan Return Saham pada Industri Telekomunikasi yang Terdaftar di Bursa Efek Indonesia - Arna Suryani (J-MAS (Jurnal Manajemen dan Sains), 2019)
This study aims to know and analyze how the effect of invesment risk on stock returns in the telecommunications industry listed in Indonesia Stock Exchange for the period 2013-2017. Invesment risk is measured by interest rate risk, market risk, inflation risk, business risk, financial risk and liquidity risk. The research method was analyzed with descriptive and using a linear regression analysis with panel data. Statistical test by testing the hypothesis F simultaneosly and t test partially, as well as to determine how much the coefficient of determanation (R2). Besed on the results of the study indicate that simultaneous investment risk has a positive and significant effect on stock returns with a large influence of 72.5%. Partially invesment risk is only market risk and business risk which has asignificant effect on stock prices, while invesment risk represented by interest rates, inflation risk, financial risk and liquidation risk does not have a sisnificant effect on stock pices. This proves that the market responds and is more interested in paying attention to market risk and business risk in valuing companies reflected in stock price